2018
DOI: 10.1111/jgh.14408
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insight, diagnosis, and treatment of ammonia‐induced hepatic encephalopathy

Abstract: Hepatic encephalopathy is a neuropsychological syndrome due to biochemical disturbance of brain function in advanced liver disease patients. Diagnosis and treatment of the condition is very demanding and has negative toll on finances with increased healthcare utilization. The pathophysiology is not completely understood; however, there is evidence that ammonia plays an important role in the etiology. Conventional methods of solely relying on blood ammonia level to diagnose hepatic encephalopathy did not help m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 62 publications
3
23
0
Order By: Relevance
“…HE is mainly due to absorption of toxic substances from the intestinal portal vein system, through the shunt without the liver first pass effect into the systemic circulation, caused by dysfunction of the central nervous system; a syndrome with mental and nervous symptoms[14]. One of the toxic substances that causes HE is blood ammonia[15]. There are two aspects of the source of blood ammonia in the body, endogenous ammonia is produced by catabolism in vivo , and exogenous ammonia is produced by catabolism of nitrogenous substances in the intestine[16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HE is mainly due to absorption of toxic substances from the intestinal portal vein system, through the shunt without the liver first pass effect into the systemic circulation, caused by dysfunction of the central nervous system; a syndrome with mental and nervous symptoms[14]. One of the toxic substances that causes HE is blood ammonia[15]. There are two aspects of the source of blood ammonia in the body, endogenous ammonia is produced by catabolism in vivo , and exogenous ammonia is produced by catabolism of nitrogenous substances in the intestine[16].…”
Section: Discussionmentioning
confidence: 99%
“…The previous literature[15] only compared the overall incidence of HE in 3 years, and showed that HE occurred one year after TIPS[32]. Therefore, we compared the occurrence of HE after 1, 3, 6, 9 and 12 mo, and the total incidence of HE after 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Increased blood ammonia levels have been considered as the main pathophysiological mechanism of HE [41,42] by causing swelling astrocytes, activation of microglia and neuroin ammation [43][44][45][46][47][48][49][50]. Microglia activation can promote the proliferation and release of pro-in ammatory cytokines [50], and the in ammation state can eventually lead to neuronal death [51].…”
Section: Discussionmentioning
confidence: 99%
“…HE is a neuropsychological syndrome caused by biochemical disturbance of brain function in advanced liver disease patients. 22 Like other neuropsychological syndromes, an increased rate of mood and anxiety disorders would not be surprising; however, the relationship between HE and depression is very complex, which can explain why different studies have reached different conclusions. Patients with cirrhosis may be under various psychosocial stresses, including relationship, occupational, and financial stress.…”
Section: Discussionmentioning
confidence: 99%